KAITAN PENCEMARAN BAKTERI COLIFORM DAN BAKTERI E-COLI PADA AIR SUMUR PENDUDUK DENGAN KEPADATAN PERMUKIMAN DI KECAMATAN JEBRES KOTA SURAKARTA TAHUN 2012 - Sri Utami, Ning (Pendidikan Geografi, 2013)
ABSTRACTThe purpose of this study were to: (1) know variations of total Pollution ofColiform and E-Coli in groundwater population in Jebres District, (2) know thefeasibility of the water Pollution of Coliform and E-Coli in District Jebres, (3) Know thePollution of the link Coliform and E-Coli with residential density in District Jebres. Themethod used is descriptive kualitatif. The research variables are factors that influencethe potential, and causes pollution Coliform and E-Coli that include population density,housing density, distance pollutant sources and shallow groundwater flow patternsadvance. Data collection techniques used include: interpretation of IKONOS imagery,field observations, and document analysis. The data analysis technique used islaboratory test match Coliform and E-Coli with water quality standards according tothe decrees. No. LH. 115 in 2003 and the Minister of Health No.492/MENKES/Per/IV/2010. The results obtained are (1) The results of the researchnote Coliform bacteria contamination is divided into three classifications namely lightblackened (samples 6 th,7 th and 17 th), blackened medium (samples 2 nd, 5 th,, and 15 th)and blackened heavy (samples 1 st, 3 rd,, 4 th. 8 th, 9 th, 10 th, 11 st, 12 nd, 13 rd,, 14 th, and16th). E-Coli Bacteria are divided into 3 levels of contamination are lightly blackened(samples 6 th, 7th and 17 th), blackened medium (samples 1 st, 2 nd, 5 th, and 15 th) andblackened heavy (sample 3 rd, 8 th, 9 th, 10 th, 11 st, 12 nd, 13 rd, 14 th, and 16 th). (2) Basedon the results of laboratory tests obtained 16 th samples and 1 st sample tapsgroundwater contaminated with Coliform and E-Coli between 3-2400 / 100 ml. (3) theresults of the research show the dense polluted Coliform bacteria and E-coli2400/100ml average, somewhat dense settlements contaminated with bacteria Coliformand E-Coli average 100/100ml, and dense settlements not contaminated with bacteriaColiform and E-coli average of 3/100 ml.The conclusions obtained are: (1) Variations of Coliform bacteriacontamination and bacteria E-Coli in District Jebres divided into three classes, namelyblackened mild, moderate and blackened blackened heavy (2) Most of the groundwaterin the District Jebres is that water unfit for consumption. (3) District Jebres classifiedas relatively densely populated areas contaminated with Coliform and E-Coli areasclassified as high and not as dense settlements are relatively polluted Coliform and EColiwith a low amount.Key Word: Wells Water, Coliform, E-Coli, Residential Density